Você está na página 1de 13

# 8 Continuous-Time

Fourier Transform

Solutions to
Recommended Problems
S8.1
(a)
x(t)

Tj
2

Tj
2

Figure S8.1-1
Note that the total width is T,.
(b)

i(t)

t
3T 1
2

-- T1

To
2

T1
2

T1
2

To
2

Tl

T 1 =O
2

Figure S8.1-2
(c) Using the definition of the Fourier transform, we have

ox(t)e -j

X(w) =

dt

Til

-T1/2

0 for

ItI>

sin wTi

12

(e -jwTI1/2

JW

Ti/2

eT1/ ) =

(e

S8-1

S8-2

T f

ak =

X(t)e

~jk

dt,

## where we integrate over any period.

ak

-T

-T
To12

(t)e -jk(2w/T)t dt = TO

T1 /2
/2

-T

e -jk(2/T

)t dt

To

ak

TO

(e

jkirToT

--

eikir1/TO) =

-jk 2,

sin kr(T1 /T 0 )
,rk

sin ,r(2k/3)
7rk

## Note that ak = 0 whenever (27rk)/3 = irm for m a nonzero integer.

(e) Substituting (21rk)/To for o, we obtain
T_1X(
TO

=2)T
I"=(21rk)/ To

1 2 sin(7rkT1 /T 0 )
To
2,rk/To

sin rk(T 1 /T 0 )
,rk

= ak

(f) From the result of part (e), we sample the Fourier transform of x( t), X(w), at
w = 2irk/To and then scale by 1/To to get ak.

## Continuous-Time Fourier Transform / Solutions

S8-3

S8.2
(a) X(w) = fx(t)e

5)e -j' dt = e ~j

(t -

-j4t dt =

= cos 5w

sin 5w,

## by the sifting property of the unit impulse.

IX(w)|

= |ej 5wI = 1

<tX(w)

= tan-'

for all w,

LIM{X(xc)}

e -a t u(t)e -i"' dt =

(b) X(w) =

- (a+jw)t

-sin5wo)

tan

e -ate -j't dt

e-

-1

dt

-5w

cos 5w

Re{X(co)}

Jawaban no.1

(a+jo)t

a+jw

## Since Re{a} > 0, e -at goes to zero as t goes to infinity. Therefore,

X(W) =

-1
1(0
a + jw

- 1) =

IX(W)I = [X(W)X*(w)]l/
Re{X(w)} =
Im{X(W)}

-X(O)

X(w) + X*(O)

1
a +jw

a +ja
a +

X(W) - X*(W)
2

a2 +

= tan-

Im{X(W))

\/

-jw)]

(2

-W
w 2 '>

= -tan

_ w

1
+o2

>

S8-4

IX(w)I

-a

4X(W)
2
Tro
-aa

2T
Figure S8.2-2

(c) X(o) =

1+12)tU(t )e

1
1 +

j(2

[ 1-+j(2-)t
-

-''' dt =
0

)0

## e[- 1+j(2-w) = 0. Therefore,

1
1 + j(o -

2)

1
IX(wO)| = [X(x)X*(W)]11 2 =
Re{X()}

Im{X(W)}

X()

1 + (w

2
X*(co)

+ (ow-

2)

X(w) + X*(W)
X(w)

\/1

tan-' ImX(W)
LRe{X(w)}

2)2

-(o - 2)
+ ((A -2)2
-tan-'(w - 2)

S8-5

X(w)I
1

4X(W)

Figure S8.2-3

S8.3

X3(t)e -' dt

(a) X3(w) =

## Substituting for x 3(t), we obtain

X 3(() =

ax 1(t)e -wt dt +

=f
=

## [ax 1 (t) + bx 2(t0)e 1-'dt

af

x 1(t)e -j dt + b f

bx 2 (t)e -jwt dt
x 2(t)e -- ' dt = aX1 (w) + bX 2 (w)

Therefore,

## Signals and Systems

S8-6

Thus,
2

1-

2,r

7rb(w -

wo)ei-' dw = ei-o'

-"oo

Note that the integral relating 2-7rS(w - wo) and e-o' is exactly of the form
X(w)ej- t dw,

x(t) =

where x(t) = e jot and X(w) = 2-7rb(co - wo). Thus, we can think of ei-o' as the
inverse Fourier transform of 2 7rb(w - wo). Therefore, 27rb(o - wo) is the Fourier

transform of eiwo'.
(c) Using the result of part (a), we have
X(M) =

1 ake

7{x(t )} = 51

2r

T,

a,

= 2,irb ( W

5{eik(2,rT)t

-21rk)

Therefore,

Z(w)

27rab

(W

k = -00

(d)
X(w)

2 sin

2 sin 2

To

Figure S8.3

S8.4

Xa(f) = X(w)
W=2,wf

We know that
x(t)

=-

X(w)e'j t do

5T {eik( 2,rs/t

S8-7

## Let w = 2irf. Then dw = 21rdf, and

1
x(t) =

X(21rf)ej 2"2ir df =

Xa(f )ei2

f= -o

27

,"f

df

IXa(f)I
TI

TI

TI

TF

T,

Figure S8.4
(b) Comparing
Xb(V)

x(t)e

= -1

jv'

and

dt

x(t

X(w) =

-j~" dt,

we see that
Xb(V) =

V2_
7r

or

X(W)

X(w) =

\7

X(w)

-V

## The inverse transform relation for X(w) is

x(t)

*0

X(w)e

=1

Xb(v)e

X2r(w)ej- dw

dw = 1
jvt

dv,

where we have substituted v for w. Thus, the factor of 1/2-x has been distributed
among the forward and inverse transforms.

S8.5

Jawaban no.2

(a) By inspection, To = 6.
(b)

ak =

TO

TO

J T0

)e

/To)t

-k(

We integrate from -3

to 3:

1 1
ak=

= 1

J-

dt

(ti + 1)+
+l 1

+ 'je

6(t) + -6(t
2

(1
-Jlk6..

+ c

Cos 2k

S8-8

(t)

(c) (i)

X 1(w)

=
-

X 2(w) =

(ii)

+ Cos 27rk

6(

x 1 (t)e -"' dt

ie * +

ie -"1

1 +

eik(2 / 6 )t

## [6(t + 1) + b(t) + -1(t - 1)]e -j't dt

+ cos w

x 2(t)e -''' dt =

## [3( t) + it(t - 1) + -3(t - 5)]e -

dt

= 1 + ie -j + le -i5 w

## (d) We see that by periodically repeating x 1 ( t) with period Ti = 6, we get t(t), as

shown in Figure S8.5-1.

x 1 (t)

-1

x 1 (t - 6)

xl(t + 6)

2
-7

t
-6

|tt)

-5

0
x(t)

-7

-6

-5

-1

Figure S8.5-1
Similarly, we can periodically repeat x 2(t) to get 1(t). Thus
S8.5-2.

T2

= 6. See Figure

## Continuous-Time Fourier Transform / Solutions

S8-9

x 2 (t)
tilt

01

X2 (t -6)

t2~ x 2 (t 6)

-6-5

X(t)

IL

-6 -5

-1

t2

t It

Figure S8.5-2
(e) Since I(t) is a periodic repetition of x 1 (t) or X 2 (0), the Fourier series coefficients
of t(t) should be expressible as scaled samples of X,(co). Evaluate X 1 ( 0 ) at w=
21rk/6. Then
co-=
Similarly, we can get
X2 -

ak

X1(x)

But e

(27rk\

k*k2rk

1
j2k/6
5e +
e

=irk1
+2o

62

njlOrk6
= e j(lOrk/62rk)
X2

=6,rk

rkI . Thus,

= 1 + cos

X6

a.

=27rk/6.

## Signals and Systems

S8-10

S8.6

(a) By inspection,

e -atu(t)

a + jw

Thus,
1

7I

e- 7tu(t)

7 + jw

Direct inversion using the inverse Fourier transform formula is very difficult.
(b)

## Xb(w) = 26(w + 7) + 26(o -

Xb(w)ej do =

Xb(t)

7),

e-
It +

7) + 6(w - 7)]ei-' dw

[6(w +

cos 7t

(c) From Example 4.8 of the text (page 191), we see that
37

alti

2a
_2a
a 2 + W2

## However, note that

ax(t)

aX(w)

since
x(t)e -jw dt = aX(w)

ax(t)e -j" dt = a
Thus,
1

-"

-e

2a

(d)

or

a2 + (02

= Xa(w)[26(o + 7) + 26(w -

Xa(w)Xb(W)

= 2X(-7)(co

2
-

XdCO)=

7 - j7

xaOt =

1f*[2
1

b(o7)

7 +j7
7+

e 7'

ir7-j7

1 1

b(co - 7)

7 +j7

7 -37

= -

XA(t)

7)]

.7 6(o + 7) +

f-

1
- e -31t
6

+ 7) + 2Xa(7)6(w - 7)

(w +7) +

27r--

9 + .2

ej_
xr7+j7

ej" do

'

Note that
1
7 +j7

7 2

-jr/4

7 -j7

=_ 1=( ,
7 2

+jir/4

Thus
XA(t)

= -

r7 -

[e -j(7t

-/4)

+ ei( 7 t-/4)]

-77r

cos

7t - -)
4

S8-11

we ~j3 w,

0 5 w < 1,

we -j w,

(e) Xe(w) =

-1

0,

(O

elsewhere,

t0,

x(t) =

X(w)e-' dw =

i [J' we -jamei'

we ~i3-ejwl dw

do -

Note that
xe"
f dx

e ax
-1)
ax
, -(ax

1

x(t)

L(
(j(t

j(t

21r

egj(t

- 3)w

- 3))

(j(t -

3)w - 1)

## which can be simplified to yield

1 [ cos (t - 3) - 1
x(t)

(t -

7r

3)2

3)w

(j )) (j(t - 3)w - 1)
(j(t - 3)) 2

sin (t - 3)

(t -

3)_

Solutions to
Optional Problems
S8.7
(a)

y(t)e -j

Y(w) =

(b) Let r

ft

-) dr e -j'' dt

x(r)h( t -

dt

Y(w)

x(r)e -'

=
=

## x(r)h(r)e -jw( r-+*T)

.fro

TT=-

d-r

dr dr

h(r)e

{r=-0

~'j

dr

X(w)H(w)

S8.8
(a) Using the analysis equation, we obtain

1 rT/2_
Ilk

I T/

-T/2

e(t)e

-jk(21r/T)

t dt-T

## Thus all the Fourier series coefficients are equal to 1/T.

(b) For periodic signals, the Fourier transform can be calculated from ak as
X(w) = 21

ak
k=-00

w-T

## Signals and Systems

S8-12

In this case,

2rk

21

PM=T

P(wj)
21Tr
T

_47

2_

_ 2n

Figure S8.8
(c) We are required to show that

2(t)

= x(t )* p(t)

x(t)* p(t) = xt

kT)

*
k

Ot

x(t) * p(t) =

[x(t) * b(t

T,

kT)]

k= -o

x(t - kT) =t(t)

x(t)* pX)O
k=

## Thus, x(t) * p(t) is a periodic repetition of x(t) with period T.

(d) From Problem P8.7, we have
X(w) = X()P(x)
=

27rk

X(-)

-T

k=

=jI

2xk

-- X(w)5(c

## Since each summation term is nonzero only at w = 27rk/T,

*0

y=)

2xk

2rk

27r

T X( T

From this expression we see that the Fourier series coefficients of t(t) are
ak =

Ti

## which is consistent with our previous discussions.

MIT OpenCourseWare
http://ocw.mit.edu

## Resource: Signals and Systems

Professor Alan V. Oppenheim

The following may not correspond to a particular course on MIT OpenCourseWare, but has been
provided by the author as an individual learning resource.